Technique and early clinical outcomes for spinal and paraspinal tumours treated with stereotactic body radiotherapy. Issue 8 (August 2015) - Finnigan, Renee; Burmeister, Bryan; Barry, Tamara; Jones, Kimberley; Boyd, Josh; Pullar, Andrew; Williams, Richard; Foote, Matthew
Abstract: We report technique and early clinical results of stereotactic body radiotherapy (SBRT) from Princess Alexandra Hospital. SBRT involves the precise delivery of highly conformal and image-guided external beam radiotherapy with high doses per fraction. It is increasingly being applied in management of spinal tumours. Thirty-six courses of spine SBRT in 34 patients were delivered between May 2010 and December 2013. Mean patient age was 58 years. Treatment was predominantly for metastatic disease, applied in de novo (n = 22), retreatment (n = 14) and postoperative (n = 8) settings. Prescribed doses included 18–30 Gy in 1–5 fractions. SBRT technique evolved during the study period, resulting in a relative dose escalation. No severe acute toxicities were observed. At median follow-up of 7.4 months (range: 1.7–22.2), no late radiation myelopathy was observed. Risk of new/worsening vertebral compression fractures was 22% (n = 8) and was significantly associated with increasing Spinal Instability Neoplastic Scores ( p  = 0.0002). In-field control was 86% with relapse occurring at a median interval of 2.8 months (range: 1.9–4.7). Thirteen patients (36%) died and median overall survival has not been reached. SBRT is an evolving technology with promising early efficacy and safety results. The outcomes of this series are comparable with international literature, and await longer follow-up.